The Poor Altmetric Performance of Publications Authored by Researchers in Mainland China - Wang, Xianwen; Fang, Zhichao; Li, Qingchun; Guo, Xinhui (Frontiers in Research Metrics and Analytics, 2016)
China's scientific output has risen precipitously over the past decade; it is now the world’s second largest producer of scientific papers, behind only the United States. The quality of China’s research is also on the rise (Van Noorden, 2016). But the online visibility and impact of China’s research are also important issues worth exploring. In this study, we investigate the altmetric performance of publications in the field of Biotechnology and Applied Microbiology and published by authors from Chinese affiliations. We find that papers published by those authors from Chinese affiliations have much lower visibility on the social web than articles from other countries. Fewer of China’s publications get tweeted, and those tweeted publications attract less social attention. A geographical analysis of tweeters shows that scholarly articles get most of their social attention from the authors’ home countries, a finding that is also confirmed by correlation and regression analysis. This situation, which is unfavorable for researchers from Chinese affiliations, is caused, in part, by the inaccessibility of mainstream social networking platforms in mainland China.